Stromal osseous metaplasia in urothelial carcinoma of the bladder: a rare case report and literature review - Joëlle Razafimahefa; Clément Gosset; Pierre Mongiat-Artus; Tsitohery Francine Andriamampionona; Jérôme Verine (BMC, 2019)
Abstract Background The bone formation within bladder tumors could be encountered in 3 conditions. These might consist of malignant bone formation in mesenchymal tumors; mixed mesenchymal and epithelial tumors; and epithelial tumors with stromal osseous metaplasia (SOM). This last is relatively rare. According to the English literature, only 12 cases have been reported in primary tumor and 7 in metastatic deposits of bladder primaries. Herein, we presented an additional case. Case presentation An 83-year-old man was admitted 13 years ago for prostatic adenocarcinoma, treated with radical prostatectomy. Biochemical recurrence was detected 2 years after surgery (prostate-specific-antigen (PSA) level: 4.60 ng/mL) and progressively normalized (<1.0 ng/mL) after adjuvant radiotherapy and annual injection of leuprorelin (enantoneR). He was referred after 8 years for hematuria, PSA level having slightly increased (0.60 ng/ml). Cystoscopy showed a nodular growth in the bladder wall, visualized as a calcified tumor on computed tomography (CT) and removed with transurethral resection. Histologically, the tumor consists of a non-muscle-invasive high grade papillary urothelial carcinoma with metaplastic bone within the stroma. Immunohistochemical analysis particularly demonstrated positive expression of respectively CD56 on osteoblasts, and CD68 on osteoclasts. MDM2 and CDK4 were negatives on osteoid and bone tissue. Six courses of Bacillus Calmette-Guerin (BCG) therapy have been administered. Two local recidives have occurred during an 8-month follow-up period after immunotherapy and were treated with six further courses of BCG therapy. At one-month follow-up, the patient was well without remaining symptoms. Conclusion SOM is a rare benign condition whose pathogenesis remains uncompletely defined. Sarcomatoïd carcinoma represents the main differential diagnosis that influences therapeutic procedures. Prognosis depends essentially on the extent of the carcinomatous component .